1991
DOI: 10.1152/jappl.1991.70.3.1337
|View full text |Cite
|
Sign up to set email alerts
|

Exercise endurance and fuel utilization: a reevaluation of the effects of fasting

Abstract: The effect of fasting on energy utilization during running or swimming was studied in adult male Wistar rats. Compared with fed rats, fasted animals displayed a decreased contribution of carbohydrates in energy supply, with decreased liver and muscle glycogen contents and decreased rate of glycogen breakdown. This was compensated by an enhanced rate of beta-oxidation. In addition, fasting induced an exaggerated sympathoadrenal response during exercise, reflected by a greater epinephrine plasma level and a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…The increased running distance with continued exercise, and the augmentation of this increase by EODF confirmed previous findings (Koubi et al, 1991;Pirke et al, 1993). Muscle contraction during exercise induces a cascade of cardiovascular and muscoskeletal adaptations resulting in improved delivery and utilization of oxygen and nutrients in the working muscles (Taivassalo et al, 2000), thus, enhancing exercise endurance (Kubukeli et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The increased running distance with continued exercise, and the augmentation of this increase by EODF confirmed previous findings (Koubi et al, 1991;Pirke et al, 1993). Muscle contraction during exercise induces a cascade of cardiovascular and muscoskeletal adaptations resulting in improved delivery and utilization of oxygen and nutrients in the working muscles (Taivassalo et al, 2000), thus, enhancing exercise endurance (Kubukeli et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…Previous findings showed that EODF induces hyperactivity in rats (Koubi et al, 1991;Pirke et al, 1993). In our experi-…”
Section: Effect Of Eodf And/or Voluntary Exercise On Physical Activitysupporting
confidence: 60%
See 1 more Smart Citation
“…A small portion (20-30 mg) of muscle or liver sample was hydrolyzed in KOH for measurement of glycogen by a method derived from Keppler and Decker 13 Catecholamines were extracted from plasma and assayed by high-pressure liquid chromatography with electrochemical detection as described previously. 14 …”
Section: Analytic Methodsmentioning
confidence: 99%
“…Plasma insulin was determined by radio immuno assay (RIA) using a speci®c kit (CIS bio international, Oris industries SA). Plasma levels of adrenaline and noradrenaline were evaluated by high-performance liquid chromatography, following the method of Koubi et al (1991). Plasma 17-û oestradiol was measured by RIA using the ESTR-CTRIA kit (CIS bio International).…”
Section: Blood Measurementsmentioning
confidence: 99%